Cell Versus Cytokine – Directed Therapies for Hemophagocytic Lymphohistiocytosis (HLH) in Inborn Errors of Immunity - Wegehaupt, Oliver; Wustrau, Katharina; Lehmberg, Kai; Ehl, Stephan (Frontiers in Immunology, 2020)
Hemophagocytic lymphohistiocytosis (HLH) is a heterogeneous hyperinflammatory syndrome with different pathways of pathogenesis resulting in similar clinical presentations. It is best defined and understood if presenting in the context of genetic immunodeficiencies associated with defects of lymphocyte cytotoxicity. In these “primary” forms of HLH, cellular and soluble immune effectors are relatively well characterized. While etoposide-based broad cell-directed therapies remain standard of care, more specific therapies targeting these effectors individually are increasingly available. Anti-CD52 as a cell-directed therapy and anti-IFN-gamma, IL-18BP and JAK-inhibition as cytokine-directed therapies are expected to broaden the therapeutic options, but the precise role of these drugs in first-line and rescue treatment indications remains to be defined. A number of additional inborn errors of immunity are associated with episodes of immune activation fulfilling the clinical criteria of HLH. Impaired pathogen control is a key driver of hyperinflammation in some conditions, while others are characterized by a strong autoinflammatory component. This heterogeneity of disease-driving factors and the variable severity in disease progression in these conditions do not allow a simple adaptation of protocols established for “primary” HLH to HLH in the context of other inborn errors of immunity. Cytokine-directed therapies hold significant promise in these increasingly recognized disorders.